The Challenge of Growth Hormone Deficiency Diagnosis and Treatment during the Transition from Puberty into Adulthood - Cianfarani, Stefano; Inzaghi, Elena (Frontiers in Endocrinology, 2013)
In children with childhood-onset growth hormone deficiency, replacement GH therapy is effective in normalising height during childhood and achieving adult height within the genetic target range. GH has further beneficial effects on body composition and metabolism through adult life. The transition phase, defined as the period from mid to late teens until 6–7 years after the achievement of final height, represents a crucial time for reassessing children’s GH secretion and deciding whether GH therapy should be continued throughout life. Evidence-based guidelines for diagnosis and treatment of GHD children during transition are lacking. The aim of this review is to critically review the up-to-date evidence on the best management of transition patients in order to ensure the correct definitive diagnosis and establish the appropriate therapeutic regimen.